Social Action Project to Enhance Entrepreneurial Competencies - Widiastuti, Anik; Wulandari, Taat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Socio-creative entrepreneurship competencies are essential for learners to have as life skills. Socio-creative entrepreneurship competence can be promoted through projects. This study aims to analyze the effectiveness of social action projects in improving learners' social-creative entrepreneurship competencies. This research is a quasi-experimental posttest-pretest non-equivalent control group design involving 57 learners in a junior high school. Data on socio-creative entrepreneurship competencies were divided into three aspects: cognitive, affective, and psychomotor. Data on cognitive aspects were collected using test techniques and instruments in the form of essay test sheets. In contrast, affective and psychomotor aspects were collected using survey techniques and instruments in the form of questionnaire sheets. The results were analyzed using inferential descriptive statistics and the Mann-Whitney U test. The pre-test, post-test, and N-gain scores were compared. The statistical analysis results showed that social action projects affect socio-creative entrepreneurship competencies. The scores achieved by students in the class that used the social action project model were higher. Therefore, the social action project model is declared